2011
DOI: 10.1007/s00268-011-1093-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Comparison of Clinical Outcomes between Endovenous Laser and Saphenous Vein‐sparing Surgery for Treatment of Varicose Veins

Abstract: The CHIVA patients had less pain postoperatively and a significantly higher sclerotherapy-free period compared to patients in the EVL group. Further follow-up studies to compare long-term results of various approaches to surgically managing varicose veins are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
2
12
0
2
Order By: Relevance
“…No guidelines exist for treating varicose veins of the leg 7 ) , and it is especially difficult to determine the appropriate treatment for advanced cases. Endovenous laser treatment is becoming common 6 ) , and while our institute is authorized by the Japanese Society of Phlebology to use that technique, our standard technique consists of high ligation, entire removal of enlarged lesions of the great and minor saphenous vein, and ligation of perforators under tumescent local anesthesia. Laser surgery, which has better cosmetic outcomes, may be as effective as high ligation 6 ) , but it is contraindicated in most of the cases our institute handles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No guidelines exist for treating varicose veins of the leg 7 ) , and it is especially difficult to determine the appropriate treatment for advanced cases. Endovenous laser treatment is becoming common 6 ) , and while our institute is authorized by the Japanese Society of Phlebology to use that technique, our standard technique consists of high ligation, entire removal of enlarged lesions of the great and minor saphenous vein, and ligation of perforators under tumescent local anesthesia. Laser surgery, which has better cosmetic outcomes, may be as effective as high ligation 6 ) , but it is contraindicated in most of the cases our institute handles.…”
Section: Discussionmentioning
confidence: 99%
“…Endovenous laser treatment is becoming common 6 ) , and while our institute is authorized by the Japanese Society of Phlebology to use that technique, our standard technique consists of high ligation, entire removal of enlarged lesions of the great and minor saphenous vein, and ligation of perforators under tumescent local anesthesia. Laser surgery, which has better cosmetic outcomes, may be as effective as high ligation 6 ) , but it is contraindicated in most of the cases our institute handles. The most common contraindication in our patient population is enlarged vein size and concomitant femoral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there were no statistical differences in recurrence or reoperations between EVLA and stripping. There are few published RCTs comparing recurrence after CHIVA and EVLA, although Chan et al 30 showed that CHIVA patients exhibited less pain and less need for sclerotherapy after operations than EVLA patients. The issue of recurrence is also a problem after foam treatment and no long term results are available for adequate comparison with other techniques.…”
Section: Recurrence Of Varicose Veinsmentioning
confidence: 99%
“…В сравнительном исследовании C. Chan и соавт. [8] доказано, что CHIVA сопровождается меньшим болевым синдромом в послеоперацион ном периоде, а оперированные пациенты нуждают ся в выполнении склерооблитерации резидуальных вен реже, чем при использовании эндовенозной ла зерной облитерации. S. BellmuntMontoya и соавт.…”
Section: лечение варикозной болезни нижних конечностейunclassified